A demographic study of clinically diagnosed patients of oral submucous fibrosis visiting ENT outpatient department of a tertiary care hospital in Muzaffarnagar district, Uttar Pradesh, India - Bhardwaj, Ramanuj; Hafiz, Aamir; Bashir, Seerat (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Oral submucous fibrosis is a premalignant condition affecting the oral cavity. It is characterized by fibrosis of the submucosal tissues, leading to restricted mouth opening, dryness, burning sensation etc. It causes significant mortality after its transformation into squamous cell carcinoma (SCC). It has now become a global health concern. Methods: The study was conducted amongst the patients aged 18-65 years who visited the ENT OPD of Muzaffarnagar Medical College with oral lesions from 01 January 2024 to 30 June 2024 (6 months). Of these patients that were clinically diagnosed with oral submucous fibrosis (OSMF), were given a detailed questionnaire and further studied. It was a hospital based cross sectional study conducted by Department of ENT and HNS, Muzaffarnagar Medical College and Hospital. Results: Of the 120 cases clinically diagnosed cases of OSMF. Mean age was 42.7 years. Most patients were in 4th and 5th decade of life and specifically in 31-40-years age range. Male to female ratio was 3.61: 1. Most patients came from rural areas. Gutkha was the most commonly used habit in these patients. M2 was the most common stage at which the patients visited the hospital. Muslims were predominant in the study population. Conclusions: OSMF is an irreversible process, it has been linked to habitual consumption of betel nut, due to its high prevalence, special emphasis should be given towards its prevention and awareness. Also, due to its increased risk of malignant transformation, prompt cessation of the particular etiological agent and early management of the disease is required. Primary healthcare professionals and dentists should be familiar with its clinical presentation, diagnosis and management.